Fire and Explosives Investigation 2015: Challenges and Opportunities - Carlysle, Felicity; Beardah, Matthew; Bryson, David; Johnson, Stephen; Nic Daeid, Niamh; Shipp, Martin (The Knowledge Transfer Network, 2015)
The Forensic Science Special Interest Group (SIG) has produced this report to provide a resource to the forensic community; identifying the challenges and opportunities within the field of fire and explosives investigation. To produce this report we brought together the fire and explosives community in a day-long workshop, comprising of presentations from a range of speakers, followed by discussion sessions directed by the challenges identified by the speakers and taken from the SIG’s “Forensic Science UK Innovation Database”. The results of these discussions have been compiled into this report.
Keywords: Fire; Explosion; Challenges